Strengthening nursing knowledge and skills in perioperative cleft care: a focused training approach in Nigeria’s surgical healthcare plan - Aiyedun Lawal, Olubunmi; Opara, Ngozika; Udeigwe-Okeke, Chisom Rachel; Obisesan, Aderonke Omoyeni; Seyi-Olajide, Justina; Aria, Oti Nimi; Adam Sheikh Abdullahi, Mohammed; Obi, Nkeiruka; Ameh, Emmanuel A. (Frontiers in Medicine, 2025)
BackgroundSafe perioperative nursing care is crucial to improving outcomes of surgical care. This is a report on the pilot implementation of a nursing training programme aimed at strengthening safe perioperative nursing care in Nigeria, aligning with the nation’s strategic framework for surgical, obstetric, anaesthesia, and nursing plan. The aim of this report is to highlight the need to incorporate perioperative nursing training into efforts to scale up access to surgical care in low resource settings.MethodsThe Nursing Care Saves Lives (NCSL) training programme which was designed for training in perioperative nursing of cleft lip and palate patients, was adapted for perioperative nursing training. A 5-day intensive training was deployed, involving lectures, hands-on activities, simulations, and group problem-solving exercises. Pre- and post-training surveys were administered, and participant feedback and 3-months follow-up assessments obtained. The data has been analysed using descriptive statistics.ResultsTwenty-six participants who were nurses involved in perioperative care, from both public and private hospitals, completed the training. Pre-training evaluation scores ranged from 23 to 72% (median 68%), increasing significantly to 61–98% (median 76%) post-training (p = 0.0001). Participants rated all training contents as useful, with high satisfaction in neonatal resuscitation and basic life support skills. Infection prevention and control, helping babies breathe, and effective communication were identified as key learnings. Recommendations for future training included facilitation skills, nutrition, and research. Although 10 (40%) participants organised step down trainings, limited funding and training materials were key barriers to step down.ConclusionThe NCSL training programme has the potential for promoting and strengthening safe perioperative nursing care. Strategic efforts are needed to scale up and expand access to this training within the wider perioperative nursing community, to enhance patient safety and surgical outcomes in the setting.